2017
DOI: 10.1080/20002297.2017.1345581
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing the dental biofilm matrix by means of fluorescence lectin-binding analysis

Abstract: The extracellular matrix is a poorly studied, yet important component of dental biofilms. Fluorescence lectin-binding analysis (FLBA) is a powerful tool to characterize glycoconjugates in the biofilm matrix. This study aimed to systematically investigate the ability of 75 fluorescently labeled lectins to visualize and quantify extracellular glycoconjugates in dental biofilms. Lectin binding was screened on pooled supragingival biofilm samples collected from 76 subjects using confocal microscopy. FLBA was then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 41 publications
1
25
0
Order By: Relevance
“…Different solid substrates with varying properties have also been used in these studies for instance human enamel in the Leeds in situ device [5,13], human enamel-dentine slab [30], bovine enamel/dentine [19,[22][23][24]31], polished glass [14,20,21,25,29,[34][35][36][37][38][39][40], hydroxyapatite discs [27,[32][33][34], or membrane filters [26]. Although the roughness of the surface of the substrate and its free energy are considered important factors for in vivo growth of the biofilm, Auschill et al [20] and Netuschill et al [41] found no major differences in the thickness of 48-h biofilm grown on enamel or glass discs.…”
Section: The Appliance and Substrates Used To Collect Biofilmmentioning
confidence: 99%
See 4 more Smart Citations
“…Different solid substrates with varying properties have also been used in these studies for instance human enamel in the Leeds in situ device [5,13], human enamel-dentine slab [30], bovine enamel/dentine [19,[22][23][24]31], polished glass [14,20,21,25,29,[34][35][36][37][38][39][40], hydroxyapatite discs [27,[32][33][34], or membrane filters [26]. Although the roughness of the surface of the substrate and its free energy are considered important factors for in vivo growth of the biofilm, Auschill et al [20] and Netuschill et al [41] found no major differences in the thickness of 48-h biofilm grown on enamel or glass discs.…”
Section: The Appliance and Substrates Used To Collect Biofilmmentioning
confidence: 99%
“…The latter workers employed either cylindrical or cuboidal form substrates. The size of the substrate was variable; as for the cylindrical discs the diameter varied from 3 mm [20][21][22]25] to 7 mm [34], while the height varied from 1 mm [14,35,36,38,40] to 4 mm [30]. Interestingly, Wood et al [13] observed significant variations in the thickness of the biofilms generated over the 4-day period between each disc, depending on the substrate architecture.…”
Section: The Appliance and Substrates Used To Collect Biofilmmentioning
confidence: 99%
See 3 more Smart Citations